Transforaminal endoscopy in lumbar burst fracture: A case report. Issue 46 (November 2017) - Wang, Yuanyi; Ning, Cong; Yao, Liyu; Huang, Xiuying; Zhao, Chengliang; Chen, Bin; Zhang, Nan
Abstract: Rationale: Lumbar burst fractures are frequent injury resulting from high-energy trauma, and the patients suffer from pain and the neurologic dysfunction. Although minimally invasive techniques have advanced rapidly, it was the first time to apply transforaminal endoscopic combined with percutaneous pedicle screw fixation to treatment of lumbar burst fractures. Patient concerns: A 33-year-old man underwent Magerl type A3.1 burst fracture at L2 and compression fractures at L3 due to falling from a height with severe lower back pain, sensory loss, and atony of the right leg. Diagnoses: Burst fracture at L2, compression fractures at L3. Interventions: The patient was presented to 1-stage operation of percutaneous pedicle screw fixation at L1, L2, L3, and L4 instead of delayed posterior open surgery. At 1 week after injury, the 2-stage operation with a percutaneous transforaminal endoscopic was undertaken for decompression. Outcomes: No matter the function of nerve and imaging findings, all got ideal recoveries in just 3 days after 2-stage operation. At the 3-month follow-up, there was no loss of sagittal plane alignment, and spinal cord compression was completely relieved. The patient regained near-full neurologic function postoperatively. Lessons: A minimally invasive surgery (ie, transforaminal endoscopic combined with percutaneous pedicle screw fixation) for the treatment of Magerl type A3.1 burst fracture at lumbar was feasible. In addition, the key to the recovery of neurological function is the complete and effective decompression of spinal.